Manajemen Karir yang Baik Perlu Diterapkan oleh Organisasi Agar Para Dosen Siap Berubah - Irma Himmatul Aliyyah; Zuryanti Zuryanti (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2018)
This study aims to study the role of human resource management in the readiness to change lecturers at Mercu Buana University. This study uses a quantitative methods and approaches with the scale used is a 1-5 Likert scale. The sample in this study amounted to 83 permanent lecturers at Mercu Buana University from the population of 456 people. In this study using two instruments, namely the scale of perception of the role of human resource management (HRM) as many as 23 items and the scale of readiness to change as many as 22 items. From the results of data analysis using the Spearmen correlation test shows that there is no role for human resource management in the readiness to change lecturers at Mercu Buana University, namely with a correlation coefficient of 0.063 and a significant value of 0.569> 0.05.